2009
DOI: 10.3855/jidc.474
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic characterization of nosocomial isolates of Staphylococcus aureus with reference to MRSA

Abstract: Background: Apart from being a major cause of mortality, nosocomial infections due to Staphylococcus aureus have been imposing a burden on patients, hospitals and health care systems. The present study was designed to determine the prevalence of methicillin resistant S. aureus (MRSA) among nosocomial isolates along with their phenotypic characterization. Methodology: MRSA and methicillin sensitive S. aureus (MSSA) were determined by performing four different tests viz: disc diffusion, oxacillin screen agar tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
32
3
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 26 publications
13
32
3
1
Order By: Relevance
“…This finding was similar to a that of a study which was done in Northern India, where out of 115 MRSA, 73% strains had shown multi-resistance [24]. Among other reports, Shrestha et al, had reported 97% MORSA [23]. However, their sample size was less (65 out of 67 strains).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This finding was similar to a that of a study which was done in Northern India, where out of 115 MRSA, 73% strains had shown multi-resistance [24]. Among other reports, Shrestha et al, had reported 97% MORSA [23]. However, their sample size was less (65 out of 67 strains).…”
Section: Discussionsupporting
confidence: 76%
“…MRSA strains with three or more non-beta lactam drug resistances have been described as multi-resistant oxacillin resistant S. aureus (MORSA) and they have been correlated with treatment failure [23]. We found that 79% MRSA isolates were multi drug resistant.…”
Section: Discussionmentioning
confidence: 65%
“…Resistance to erythromycin, sulfamethoxazole-trimethoprim and clindamycin reached 58%, 43% and 28%, respectively. Particularly among the MRSA, the prevalence of resistant to those antibiotics was very elevate (87%, 83% and 60%, respectively) in comparison to the rates reported in previous studies [20][21][22]. Nowadays, it is common to see such resistance profiles, especially against clindamycin, due to haphazard use of these antibiotics [22].…”
Section: Resultsmentioning
confidence: 63%
“…Other studies have also reported high prevalence of MRSA in clinical samples [20][21][22]. Nowadays, vancomycin is used as drug of choice for treating MRSA, but the emergence of vancomycin intermediate-sensitive S. aureus (VISA) and vancomycin-resistant S. aureus (VRSA) has limited even this therapeutic route [2].…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have also reported high prevalence of MRSA in clinical samples [20][21][22]. Nowadays, vancomycin is used as drug of choice for treating MRSA, but the emergence of vancomycin intermediate-sensitive S. aureus (VISA) and vancomycin-resistant S. aureus (VRSA) has limited even this therapeutic route [2].…”
Section: Resultsmentioning
confidence: 99%